Vibration of Tensegrity Stucture by using SEM - Buntara Sthenly Gan; Shota Kiryu (JACEE (Journal of Advanced Civil and Environmental Engineering), 2019)
A tensegrity structure is a structure which consists both of compressive and tensile elements without being restrained at the boundaries. The self-equilibrium state inside the tensegrity structure is the condition that builds the structure without any boundary condition necessity. The conventional Eigensystem solver cannot deal with this kind of structure since there are rigid body motions in the governing equations. The exact dynamic solution of tensegrity structure problems can only be obtained by using the frequency-dependent dynamic method. In this study, the free vibrational characteristics of a tensegrity structure which is modeled by a combination of the compressive strut and tensile cables elements are solved by using the Spectral Element Method (SEM). Natural frequencies of the tensegrity are tracked by using the Wittrick-Williams algorithm. Numerical calculations are given to show the effectiveness, efficiency, and accuracy of the SEM in solving the axially vibrating members of the tensegrity structures.